Antifungal Activity from Garlic Extract (Allium sativum) Against Candida albicans Growth - Agustantina, Titien Hary; Soekartono, R. Helal (Indonesian Journal of Dental Medicine, 2021)
Background: The accumulation of food waste and plaque causes Candida albicans development, which causes the product of Candida albicans' endotoxin to rise and enter into the mucous membrane, producing inflammation known as denture stomatitis. Many natural ingredients have been transformed into medications, including Allium sativum (garlic), which includes antibacterial allicin components. Purpose: The purpose of this study was to investigate inhibitory activity of A. sativum extract toward C. albicans growth. Methods: The sample used in this investigation was A. sativum extract at various concentrations of 5%, 25%, 50%, and 75%. The sample was separated into five groups: 5%, 25%, 50%, and 75% A. sativum extract, with plain A. sativum extract serving as the control group. Each group has three specimens. One way analysis of variance (ANOVA) and Tukey honest significant different (HSD) were used to evaluate the data (p<0.05). Results: There was significant difference of 5%, 25%, 50%, and 75% A. sativum extract towards C. albicans growth. Conclusion: The highest antifungal activity on Candida albicans growth was found in 75% Allium sativum extract.